Effects of Dimethyl Fumarate on the Karnofsky Performance Status and Serum S100Î² Level in Newly Glioblastoma Patients: A Randomized, Phase-II, Placebo, Triple Blinded, Controlled Trial: - Shafizadeh, Milad; Jangholi, Ehsan; Rostami, Mohsen; Maroufi, Seyed Farzad; Bereimipour, Ahmad; Majidi, Shahram; Mohebbi, Niayesh; Khoshnevisan, Alireza (Galen Medical Journal, 2022)
Background: Glioblastoma (GBM) is the most common primary central nervous system malignancy with a low survival without extra logistics. Currently, there is no definitive chemotherapy among the studied options. This study aims to evaluate the neuroprotective effects of dimethyl fumarate (DMF) on surgical brain injuries in patients treated for GBM. Materials and Methods: This randomized, phase II, placebo, triple-blinded, controlled trial was performed on 36 patients with a diagnosis of GBM. All the patients received DMF (240 mg, three-times per day) or placebo (with the same shape and administration route) one week before surgery. Also, patients in both groups after the operation received standard treatments (radiotherapy plus chemotherapy). In addition, Kanofsky's performance status (KPS) score was evaluated at baseline and one month later. Also, serum S100Î² was measured 48 hours before and after surgery. Results: There was no significant difference among DMF and control groups with regard to age, gender, and the extent of resections (PËƒ0.05). The most adverse event in both groups was a headache. Although the serum S100Î² level was not markedly changed after surgery, the mean KPS in the DMF group was higher than in the control group after surgery. Conclusion: The DMF could be a possible good regime for the treatment of GBM; however, questions are raised regarding its efficacy and application for the addition to standard treatment.[GMJ.2022;11:e1897]